PENGALAMAN SELF REGULATED LEARNING SISWA UNTUK MENGHADAPI UJIAN - Sudinadji, Muh Bagus; Kumaidi, Kumaidi (Indigenous, 2019)
The completeness of a program in the education unit (in this case secondary school) will end with the holding of an evaluation of learning outcomes or exams, which are school exams and national exams, students will increase their learning activities in preparation for being able to take exams and try to produce satisfying achievements. This study aims to explain students? experiences in practicing self-regulated learning (SRL), which includes students? readiness in an active, constructive process, able to set learning goals, monitor, regulate, and control cognition, motivation, and behavior. This study uses a qualitative approach with data collection methods in the form of a focused group discussion (FGD) and essay writing on seven main informant students, plus interviews with seven supporting informants (subject friends). The informants in this study are students of class XII who have taken the school exams and national exams. The results of this study explain that the experience of SRL in students, in behavior, motivation, and cognitive (learning strategies), still requires an increase in the problem of time management, planning, and targets. Internally, the suitability of SRL is motivated by habits, motivation, and goals, while externally influenced by culture, parenting, and the environment. SRL is a managerial skill in learning because it regulates learning resources so that they can be taught or trained as early as possible to optimize academic skills and academic adjustment of students in the future.Keywords : exam; self-regulated learning; studentKetuntasan suatu program pada satuan pendidikan (dalam hal ini sekolah menengah) akan diakhiri dengan diselenggarakannya evaluasi hasil belajar atau ujian, yaitu ujian sekolah dan ujian nasional, siswa akan meningkatkan aktivitas belajarnya sebagai persiapan diri untuk dapat mengikuti ujian dan berusaha untuk menghasilkan prestasi yang memuaskan. Penelitian ini bertujuan untuk menjelaskan pengalaman siswa dalam mempraktekkan self-regulated learning (SRL), yang meliputi kesiapan siswa dalam proses  yang  aktif,  konstruktif, mampu menetapkan  tujuan belajar, memonitor, mengatur, dan  mengontrol kognisi, motivasi,  serta perilaku. Penelitian ini menggunakan pendekatan kualitatif dengan metode pengumpulan data berupa focused group discussion (FGD) dan tulisan karangan pada tujuh siswa informan utama, ditambah dengan wawancara pada tujuh informan pendukung (sahabat subyek). Informan  dalam penelitian ini adalah siswa kelas XII yang sudah menjalani ujian sekolah dan ujian nasional. Hasil penelitian ini menjelaskan bahwa pengalaman SRL pada siswa, secara perilaku, motivasi, dan kognitif (strategi belajar), masih memerlukan peningkatan pada masalah pengaturan waktu, perencanaan, serta target. Secara internal, kesesuaian SRL dilatarbelakangi oleh kebiasaan, motivasi, dan tujuan, sedangkan secara eksternal dipengaruhi oleh budaya, pola asuh, dan lingkungan. SRL merupakan ketrampilan manajerial dalam belajar karena mengatur sumberdaya belajar sehingga dapat diajarkan atau dilatihkan sedini mungkin untuk mengoptimalkan ketrampilan akademis dan penyesuaian akademis siswa di waktu yang akan datang.Kata kunci: self-regulated learning; siswa; ujian.